UK industry gets mobile with water filtration. Issue 1 (January 2018) - Unknown
Abstract : Mobile containerised water filtration plants have been a popular overseas for many years. The UK has been slow to pick up on the advantages of this type of plant deployment option, but it is now becoming a rapidly increasing trend.